Completion Design for The Development of a Multi-Layer and Multi Fluid Reservoir Systemin Offshore Well AA-01, North-West Java - Wijoyo Niti Daton; Vincent Chandra; Steven Chandra (Journal of Earth Energy Engineering, 2021)
Completion systems are important components of hydrocarbon field development. As the link between the reservoir and surface facilities, completions need to be designed to maximize hydrocarbon recovery and withstand consistently changing conditions for years, within the safety requirements. However, designing completion for a well comprising a multi-layer and multi-fluid reservoir is quite challenging. The completion design must use the right materials and be able to safely produce single, as well as commingle products, and add any artificial lifts, depending on the method with the most optimum value. This paper, therefore, discusses the model development of completion design for an offshore well AA-01, one of the offshore wells with multi-layer and multi-fluid reservoir systems in Indonesia. Well AA-01 penetrates two productive layers, the upper layer AA-U1, and the lower layer AA-L2. The upper layer is a gas reservoir with initial gas in place of 1440 MMSCF, while the lower layer is an oil reservoir with initial oil in place of 6.1 MMSTB. In addition, the model design used available field data, for instance, PVT and DST, from well X. The base well completion was also used to model the completion design in software. Meanwhile, commercial software was utilized to estimate the well hydrocarbon recovery. Subsequently, several designs were tested, and the design with maximum production as well as hydrocarbon recovery was selected. The completion design selected comprises 9⅝ inch 47 ppf L-80 production casing, as well as 7⅝ inch 29.7 ppf L-80 liner, and produced commingle with oil and gas recovery of about 50.16% and 92.3%, respectively, in 5 years production